A Glial‐Silicon Nanowire Electrode Junction Enabling Differentiation and Noninvasive Recording of Slow Oscillations from Primary Astrocytes. Issue 4 (18th February 2020) - Saracino, Emanuela; Maiolo, Luca; Polese, Davide; Semprini, M.; Borrachero‐Conejo, Ana Isabel; Gasparetto, Jacopo; Murtagh, Stefano; Sola, Margherita; Tomasi, Lorenzo; Valle, Francesco; Pazzini, Luca; Formaggio, Francesco; et al.
Abstract: The correct human brain function is dependent on the activity of non‐neuronal cells called astrocytes. The bioelectrical properties of astrocytes in vitro do not closely resemble those displayed in vivo and the former are incapable of generating action potential; thus, reliable approaches in vitro for noninvasive electrophysiological recording of astrocytes remain challenging for biomedical engineering. Here it is found that primary astrocytes grown on a device formed by a forest of randomly oriented gold coated‐silicon nanowires, resembling the complex structural and functional phenotype expressed by astrocytes in vivo. The device enables noninvasive extracellular recording of the slow‐frequency oscillations generated by differentiated astrocytes, while flat electrodes failed on recording signals from undifferentiated cells. Pathophysiological concentrations of extracellular potassium, occurring during epilepsy and spreading depression, modulate the power of slow oscillations generated by astrocytes. A reliable approach to study the role of astrocytes function in brain physiology and pathologies is presented. Abstract : The bioelectrical activity of non‐neuronal cells called astrocytes is essential for the brain function. Here it is demonstrated that a forest of randomly oriented gold coated‐silicon nanowires (Au/SiNWs) induces the differentiation of astrocytes showing complex structural and functional properties they express in vivo. Tight junctions between the Au/SiNWs‐device and astrocytes processes enable extracellular recording of slow‐frequency oscillations generated only by differentiated cells.